On the Innovation of Higher Vocational Physical Education Guided by Vocational Education - Jia, Yuzhi (Transactions on Economics, Business and Management Research, 2024)
Higher Vocational College is an important strategic position to cultivate applied talents in the field of education in China, and physical education is an essential course in higher vocational colleges. From the perspective of vocational education background, physical education curriculum education in higher vocational colleges should be improved and innovated with the change of educational objectives and teaching forms, to ensure higher efficiency and quality of personnel training. Therefore, this paper mainly discusses the innovation and development of physical education in Higher Vocational Colleges with vocational education as the leading background, with the purpose of promoting personnel training to a higher level, making students more professional and professional, to promote students’ vocational skills and have better core competence in social work in the future.